Equity in new active travel infrastructure: A spatial analysis of London's new Low Traffic Neighbourhoods. (October 2021) - Aldred, Rachel; Verlinghieri, Ersilia; Sharkey, Megan; Itova, Irena; Goodman, Anna
Abstract: In this article we examine equity in new active travel infrastructure in London, UK. We focus on Low Traffic Neighbourhoods (LTNs) introduced during Covid-19. These area-based schemes mainly involve 'modal filters' that restrict through motor traffic from residential streets within a neighbourhood. Such approaches to traffic management are traditional in the Netherlands, but are relatively novel in London and other global cities such as Barcelona. LTNs are often controversial, with one criticism being that they are implemented in affluent areas and hence benefit richer residents. London represents an excellent opportunity to investigate whether these rapidly introduced schemes have so far been equitably distributed. We focused on LTNs introduced between March and September 2020 and still present at the end of October 2020. Having generated datasets representing these new LTN locations and their boundary roads, we matched these to Output Areas (OAs, administrative areas containing around 300 residents). We then examined the extent to which LTN implementation was associated with age, ethnicity, disability, employment and car ownership (using Census 2011 data) and small-area deprivation (using the Index of Multiple Deprivation 2019). We estimated that 3.7% of all Londoners live inside a new LTN, and 8.9% live within 500 m walking distance of a new modal filter. Across London as a whole, people in the most deprived quarter of OAs were 2.5 times more likely to live in a new LTN, compared to Londoners in the least deprived quarter. While overall Black, Asian and Minority Ethnic (BAME) people were slightly more likely than White Londoners to live in a new LTN, this varied by ethnic group. Specifically, Black Londoners were somewhat more likely, and Asian Londoners somewhat less likely than White people to live in a new LTN. Car-free households were more likely to live in a new LTN. We also examined equity within London's districts, which lead on implementation of LTNs. In the median district, people in more deprived areas were more likely to live in an LTN than people in less deprived areas, suggesting that, on average, individual districts have prioritised their more deprived areas. However, in the median district, BAME residents were slightly less likely to live in an LTN than White residents. Across districts implementing LTNs there was wide variation, with some much more or less equitable than others. A third of districts implemented no LTNs at all. Finally, at the micro level, residents living in LTNs were demographically similar to neighbours living in OAs that touched an LTN boundary road. We conclude that LTN implementation has been broadly equitable at the city and micro levels, but the picture is more mixed at the district level, despite districts being encouraged to consider deprivation when planning LTN locations. Equity metrics should be used in policy and research to monitor and improve the distribution of active travel interventions. Highlights: Article examines equity of new Low Traffic Neighbourhood (LTN) implementation in London, UK, March–September 2020. Across London, people in deprived areas were 2.5 times more likely to live in a new LTN than people in less deprived areas. Across London, households without a car were 1.6 times more likely than car owners to live in an LTN. At the micro-level, LTN residents were demographically similar to neighbours in nearby boundary areas. London's devolved governance means equity at pan-London and micro-level can co-exist with a mixed picture at district-level.